Discovery of Indosialis from China, with description of one new species (Megaloptera: Sialidae) - Liu, Xing Y.; Yang, Ding; Hayashi, Fumio (Zootaxa, 2006)
The little known alderfly genus Indosialis is recorded from China for the first time. One species is described as new to science: Indosialis bannaensis sp. nov.